The effect of corporate income tax on the economic growth rates of the Canadian provinces - Ferede, Ergete; Dahlby, Bev (My University, 2019)
This paper investigates the long-run effects of the corporate income tax (CIT) rate on the economic growth of Canadian provinces using annual panel data for the period 1981-2016. We find evidence of a statistically significant negative long-term relationship between the provincial statutory CIT rate and economic growth. The model has the properties of a neo-classical growth model in that a reduction in the CIT rate “temporarily” increases the growth rate of the economy before returning to its long-run run growth rate. However, the temporary growth effects are economically significant and persistent. According to our preferred specification of the econometric model, one percentage point reduction in a provincial government’s statutory CIT rate increases the growth rate by 0.12 percentage points four years after the initial CIT rate cut and increases real per capita GDP by 1.2 percent in the long-run. We use the model to simulate the recently announced reduction in the CIT rate in Alberta from 12 percent in 2018 to 8 percent in 2022. The simulation results indicate that the growth rate of real per capita GDP would increase by 0.92 percentage points in 2022 and by 0.28 percentage points in 2029. The model also predicts that real per capita GDP would be 2.5 percent higher in 2022 and 6.5 percent higher in 2029. This would translate into employment increases of approximately 58,000 in 2022 and 172,000 by 2029. Our results indicate that provincial governments could significantly improve economic performance by lowering provincial corporate income tax rates.
Keywords: corporate income tax; CIT; economic growth; Canadian provinces; neo-classical growth model; long-run run growth rate; econometric model; GDP; employment increases; provincial statutory rate